NALAR âIRFÄNÄª: TRADISI PEMBENTUKAN DAN KARAKTERISTIKNYA - Nasrullah, Nasrullah (Hunafa: Jurnal Studia Islamika, 2012)
Abstract: It must be acknowledged that the Islamic world until these days has left far behind from the West in terms of achievement in science and technology as a result of a burhÄnÄ«-based system of knowledge that is rational-empirical. Therefore, Muslims must take back a burhÄnÄ« tradition that was once victorious in the golden age of Islam in the past. But the West that has been advanced with its civilization âstabbedâ and âkilledâ the civilization they had built themselves. This is due to the fact that the standard of truth is based on the arrogance and supremacy of the rational-empirical reasoning as such, while bayÄnÄ« (textual) and âirfÄnÄ« (spiritual) reasonings are alienated or marginalized, although it is clear that human life cannot be be measured only on the criteria of empirical rationalism, but it needs textual and spiritual approaches.Kata Kunci : epistemologi, irfani, burhani, bayani, Timur, BaratÂ